Pemaknaan Simbol Representasional Lintas Agama: Sebuah Upaya Merumuskan Alur Rekursif Imposisi Makna Simbol - Alexander, Michael (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2020)
Representational symbols of religious identity are open resource of meaning. Instead of reconstructing meaning, interpretation is a recollection of cultural traditions. Therefore, disputes over symbols occur because of conflicting values, perceptions, and worldviews. However, cultural traditions are not static dogmas preserved in religious cultural memory. They are dynamic because they are also influenced by contemporary relations between groups. This paper argues for the fluidity of construction meaning of symbols and the role of social interaction and synthesize two ideas. First, Roland Barthes' view on a social semiotic approach to representational symbol will be raised. Second, the idea of symbolic interaction that meaning is a social construction, defined through interactions between collectives, and manifested in the form of actions following interpretations that arise within the subject of meaning. Finally, the author will formulate a recursive semiotic model as a synthesis of the two discussed approaches. The fluidity of meaning will appear through the definition and redefinition that occur in the recursive process. The conclusion to be drawn is that social relations are the key to the formulation of symbolic meaning.